Fear, society, and the police - June, Dale L. (Routledge, 2020)
Fear, society, and the police -- Introduction to fear -- Antecedents of fear -- Handling fear -- Fearful societies of the past -- Fear in contemporary society -- Living in a world of fear -- Terror and fear of the unknown -- Modern society and the police -- Victims and fear of violent crime -- Fear and the news media -- Mean streets and shootings -- Anger and fear -- Police subculture and personality -- Racism or fear -- Reality and the brain -- PTSD in law enforcement and counter viewpoints of policing.